2016
DOI: 10.2217/nnm.16.14
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and Pharmacokinetics of Mad2 siRNA-loaded EGFR-Targeted Chitosan Nanoparticles in Cisplatin Sensitive and Resistant Lung Cancer Models

Abstract: Background: The present study focuses on biodistribution profile and pharmacokinetic parameters of EGFR-targeted chitosan nanoparticles (TG CS nanoparticles) for siRNA/cisplatin combination therapy of lung cancer. Material & methods: Mad2 siRNA was encapsulated in EGFR targeted and nontargeted (NTG) CS nanoparticles by electrostatic interaction. The biodistribution of the nanoparticles was assessed qualitatively and quantitatively in cisplatin (DDP) sensitive and resistant lung cancer xenograft model. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 66 publications
1
43
0
Order By: Relevance
“…These nanoparticles show a high polydispersity index (PDI), which is consistent with natural polymers such as chitosan primarily since they have a higher degree of variation in chain length. We have always observed and reported a high PDI for these nanoparticles in all our previous work [[23, 33, 37]] and the same has been reported in literature as well [38, 39]. …”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…These nanoparticles show a high polydispersity index (PDI), which is consistent with natural polymers such as chitosan primarily since they have a higher degree of variation in chain length. We have always observed and reported a high PDI for these nanoparticles in all our previous work [[23, 33, 37]] and the same has been reported in literature as well [38, 39]. …”
Section: Resultssupporting
confidence: 84%
“…Interestingly, our biodistribution and pharmacokinetic studies using the NTG and TG nanoparticles in the same tumor models revealed that TG system has tumor exposure than the NTG system and also demonstrate better targeting efficiency [37], we do not see a corresponding increase in efficacy. The in vitro data also corroborate that TG nanoparticles are able to internalize more efficiently than the NTG nanoparticles [23].…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…In a different study, EGFR-targeted chitosan nanoparticles successfully delivered a combination of cisplatin and Mad2 siRNA in cisplatin-sensitive and -resistant in vivo lung cancer models. Cisplatin-resistant tumors showed improved tumor inhibition with EGFR-targeted combination therapy, which showed reduced toxicity to normal tissues [119]. …”
Section: Polymeric Nanoparticles For Receptor-mediated Gene Delivery mentioning
confidence: 99%